Whole exome sequencing approach to childhood onset familial erythrodermic psoriasis unravels a novel mutation of CARD14 requiring unusual high doses of ustekinumab - S. Signa; E. Campione; M. Rusmini; S. Chiesa; A. Grossi; A. Omenetti; R. Caorsi; G. M. Viglizzo; M. Galluzzo; L. Bianchi; M. Talamonti; A. Orlandi; et al. (BMC, 2019)
Abstract Background Autosomal dominant gain of function mutations in caspase recruitment domain family member 14 (CARD14) is a rare condition associated with plaque-type psoriasis, generalized pustular psoriasis, palmoplantar pustular psoriasis and pityriasis rubra pilaris. Recently, a new CARD14 -associated phenotype defined as CAPE (CARD14-associated papulosquamous eruption) with clinical features of both psoriasis and pityriasis rubra pilaris was reported. We describe a family carrying a novel heterozygous mutation in CARD14 gene, with childhood-onset erythrodermic psoriasis requiring an unusual extremely high dose (up to 2 mg/kg every 8 weeks) of ustekinumab to achieve disease remission. Case presentation We describe a large family with three pairs of twins presenting a clinical phenotype characterized by childhood-onset erythrodermic psoriasis; in some family members is also reported psoriatic arthritis. The two probands presented poor clinical response to topic and systemic therapy with antihistamine, steroid, retinoids, cyclosporine and etanercept. After exclusion of the most common genes associated to autoinflammatory diseases (IL36RN, IL1RN, MVK, TNFRSF1A, NLRP3, NLRP12, MEFV, NOD2, PSMB8, PSTPIP1, LPIN2) we approached a new gene search by subjecting to Whole Exome Sequencing (WES) analysis five members of the family. A novel heterozygous mutation (c.446 T > G, leading to the missense amino acid substitution p.L149R) in the exon 4 of the CARD14 gene was identified in all affected members. Increasing dosages (up to 2 mg/kg every 8 weeks) of ustekinumab, a human monoclonal antibody targeting interleukin-12 (IL-12) and interleukin-23 (IL-23), allowed the complete control of the clinical manifestations, with an evident reduction of circulating Th17 and Th22 CD4+ T cell subsets. Conclusions We describe the association of mutations of the CARD14 gene with an erythrodermic psoriasis pedigree, underlying the necessity to investigate CARD14 mutations in childhood-onset psoriasis cases and confirming the presence of CARD14 causative mutations also in erythrodermic psoriasis form, as recently reported. Also in pediatric age, ustekinumab represents a powerful therapeutic option for this rare condition, that is usually refractory to other treatments. In young children, high and frequent dosages allowed a complete control of the clinical manifestations without any severe side effects, with a long-term follow-up.